Bnei Noah: History, Theory, and Practice. - Polonsky, Pinchas; Akhiezer, Golda (Modern Judaism: A Journal of Jewish Ideas & Experience, 2021)
The concept of Bnei Noah originated in ancient times. Throughout history it has remained purely theoretical, however, in recent times, we are witnessing tentative steps towards its practical implementation. The Bnei Noah is an emerging movement in a variety of countries. As such, Noahism now has practical halakhic and social implications. Our research focuses on changes in perception of Bnei Noah in the context of modern Judaism and the state of Israel. This is a first attempt to explore the characteristics, tendencies, and motivations of the contemporary Noahide movement.